Lithium cobalt oxide positive electrode material with O2 phase structure as well as preparation method and application of lithium cobalt oxide positive electrode material
By preparing the O2 phase lithium cobalt oxide positive electrode material with P63mc space group structure, the problems of cycle stability and safety of lithium cobalt oxide materials are solved, and high energy density and safety performance are improved.
Patent Information
- Application Number
- CN202411477719.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing lithium cobalt oxide materials have fast capacity decays during the charge and discharge cycle, and there is a risk of structural damage and thermal runaway, making it difficult to meet the needs of high energy density and high safety batteries.
Provided is a lithium cobalt oxide cathode material with an O2 phase structure, and its chemical formula is Li1+a(CocMd)(1+a)/(1+a+b)O2·Xb(CocM'd)b/(1 +a+b)O2, with a P63mc space group structure, is prepared by a combination of specific cobalt source materials, lithium compounds and elements, using high-temperature calcination and ion exchange methods to form a material with excellent cycling stability and thermal stability.
The high voltage cycle stability and safety performance of lithium cobalt oxide cathode material is achieved, the energy density and safety performance of the battery are improved, and the cycle retention rate and capacity output are significantly improved.
Smart Images

Figure CN119153664A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery positive electrode materials, and in particular to a lithium cobalt oxide positive electrode material with an O2 phase structure, and a preparation method and application thereof. Background Art
[0002] As the global demand for clean energy and sustainable development continues to increase, the new energy industry has become one of the focuses of attention. In the new energy industry, lithium-ion batteries, as a high-energy-density, lightweight, and environmentally friendly energy storage technology, have become the main energy storage device and are widely used in electric vehicles, energy storage systems, and portable electronic products. Lithium cobalt oxide is one of the positive electrode materials of lithium-ion batteries. It has high capacity, high voltage, and high cycle life, so it plays an important role in lithium-ion batteries.
[0003] The lithium cobalt oxide material used in commercial applications belongs to the hexagonal system, with a layered crystal structure and belongs to the space group R-3m. Each lithium cobalt oxide unit cell contains a cobalt ion (Co 3+ ) layer and two lithium ions (Li + ) layer. The cobalt ion layer is composed of octahedrons, and each cobalt ion is surrounded by six oxygen ions (O 2- ). The lithium ion layer is composed of octahedrons and tetrahedrons, and each lithium ion is surrounded by six oxygen ions. This layered structure gives lithium cobalt oxide materials good ion diffusion performance and conductivity, which is conducive to high-speed charging and discharging of batteries. Lithium cobalt oxide materials have relatively high electrode potential and specific capacity, that is, they can provide higher voltage output, so that more lithium ions can be stored per unit mass or volume. At the same time, lithium cobalt oxide materials have good cycle stability and life, and can maintain relatively high battery performance in multiple charge and discharge cycles.
[0004] However, lithium cobalt oxide materials still have certain limitations. The capacity of traditional lithium cobalt oxide decays rapidly during the charge and discharge cycle. This is mainly due to the large range of changes in the oxidation state of cobalt ions in the traditional lithium cobalt oxide structure, which causes large volume expansion and contraction of cobalt ions during the charge and discharge process, thereby causing damage to the crystal structure and capacity loss. Structural changes may lead to the accumulation of internal stress in the material, increase the risk of thermal runaway of the battery during the cyclic charge and discharge process, and there are certain safety hazards. Therefore, lithium cobalt oxide is prone to thermal runaway reactions at high temperatures, resulting in safety problems such as combustion or explosion of the battery. At present, the methods for modifying lithium cobalt oxide mainly include two technical means: doping and coating. By introducing doping with other elements, such as aluminum, nickel, magnesium, etc., the composition and structure of lithium cobalt oxide can be changed, its electronic structure and ion diffusion behavior can be adjusted, and the cycle life of the battery can be improved; the lithium cobalt oxide particles are coated with coating materials to form a protective layer to enhance its structural stability, inhibit the dissolution of cobalt ions and prevent adverse reactions of the battery, thereby improving the cycle life and safety performance of the battery. However, the above method still has certain problems. Doping will cause lattice distortion of lithium cobalt oxide, resulting in reduced safety performance and limited capacity, while coating will also lead to a decrease in the specific capacity of lithium cobalt oxide.
[0005] In summary, the lithium cobalt oxide currently available on the market has problems such as cycle stability and limited capacity, and it is difficult to meet the industry's demand for high energy density and high safety batteries. Summary of the invention
[0006] The purpose of the present invention is to provide a lithium cobalt oxide positive electrode material with an O2 phase structure and a preparation method and application thereof in view of the defects of the prior art. The lithium cobalt oxide positive electrode material provided by the present invention has a very good pure phase structure, a small lattice change, and excellent cycle stability under high voltage. At the same time, when applied to batteries, it has better thermal stability and safety performance, and can greatly improve the energy density of the battery.
[0007] To achieve the above objectives, in a first aspect, an embodiment of the present invention provides a lithium cobalt oxide positive electrode material with an O2 phase structure, wherein the general chemical formula of the lithium cobalt oxide positive electrode material is: Li 1+a (Co c M d ) (1+a) / (1+a+b) O2·X b (Co c M ’ d ) b / (1+a+b)O2, wherein -1<a≤0.1, 0<b≤1, 0<c≤1, 0≤d≤0.5, -1<a+b≤1.1, X comprises one or more elements selected from Na, K, Rb, Cs or B, and M and M' are both selected from at least one element selected from Ni, Mn, Al, Mg, Co, Cu, Ca, Zn, Zr, B, Nb, Fe, Cr, Y, La, Ce, Cd or Al;
[0008] The space group of the lithium cobalt oxide positive electrode material is P63mc;
[0009] The lithium cobalt oxide positive electrode material is tested by X-ray using a Co-Kα target material. A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 = There are characteristic diffraction peaks at the positions of 16.0-16.5°;
[0010] The lithium element in the lithium cobalt oxide positive electrode material comes from a lithium compound.
[0011] Preferably, the lithium compound includes a first lithium compound and a second lithium compound; wherein the first lithium compound is lithium nitrate; the second lithium compound includes: one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium iodide, lithium fluoride, lithium bromide, and lithium phosphate;
[0012] The molar ratio of the amount of the second lithium compound added to the total amount of the first lithium compound and the second lithium compound added is N; wherein N=m(LiY) / n(LiY+LiNO3), m represents the molar content of the second lithium compound, n represents the sum of the molar contents of the first lithium compound and the second lithium compound, LiY represents the abbreviation of the second lithium compound, and 0.2≤N≤0.6;
[0013] The lithium cobalt oxide positive electrode material has a 2θ A1 The peak intensity of the characteristic diffraction peak at is I A1 , in 2θ B1 The peak intensity of the characteristic diffraction peak at is I B1 ;
[0014] I A1 , said I B1 The following relationship is satisfied with N:
[0015] k·(I A1 / I B1 )=2.393-(N-0.4) 2 , where k is the correction coefficient, 0.9≤k≤1.1.
[0016] Preferably, it is characterized in that the morphology of the lithium cobalt oxide positive electrode material is a secondary single crystal particle; the secondary single crystal particle is formed by a plurality of primary flaky particles; the thickness of the primary flaky particles is between 0.7 μm and 3.7 μm.
[0017] Preferably, the median particle size D50 of the secondary particles of the lithium cobalt oxide positive electrode material is 2 μm to 18 μm, preferably 4 μm to 15 μm;
[0018] The specific surface area of the lithium cobalt oxide positive electrode material is 0.5 m 2 / g~1.0m 2 / g, preferably 0.6m 2 / g~0.9m 2 / g;
[0019] The true density of the lithium cobalt oxide positive electrode material is 2 g / cm 3 ~6g / cm 3 , preferably 3g / cm 3 ~5g / cm 3 ;
[0020] The residual alkali on the surface of the lithium cobalt oxide positive electrode material is 0.5% to 2.5%, preferably 1% to 2%, based on the weight of the lithium cobalt oxide positive electrode material.
[0021] Based on the weight of the lithium cobalt oxide positive electrode material, the free sodium content of the lithium cobalt oxide positive electrode material is 0.5% to 2.5%, preferably 0.6% to 1.5%.
[0022] In a second aspect, an embodiment of the present invention provides a method for preparing the lithium cobalt oxide positive electrode material with an O2 phase structure as described in the first aspect, the preparation method comprising:
[0023] Step S1, uniformly mixing a cobalt source material, a sodium source material, a material containing an M element, and a material containing an M' element according to a certain proportion to obtain a mixed material;
[0024] Step S2, calcining the mixture at high temperature to obtain an intermediate product;
[0025] Step S3, weighing a certain amount of lithium compound and dissolving it in pure water to obtain a lithium compound aqueous solution;
[0026] Step S4, weighing the intermediate product according to a certain Li / Na molar ratio, adding it to the lithium compound aqueous solution for ion exchange, and obtaining an ion exchange product;
[0027] Step S5, washing and drying the ion exchange product to obtain a lithium cobalt oxide positive electrode material.
[0028] Preferably, the cobalt source material includes one or more of cobalt oxide, cobaltous oxide, cobalt trioxide, cobalt chloride, cobalt sulfate, cobalt hydroxide, cobalt oxalate, cobalt carbonate, and organic acid cobalt; the median particle size D50 of the cobalt source material is 1 μm to 20 μm, and the specific surface area is 2.5 m 2 / g~5.5m 2 / g, tap density is 2.0g / cm 3 ~3.2g / cm 3 ;
[0029] The sodium source material includes: one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium nitrate, sodium oxide, sodium peroxide, sodium sulfate, and sodium chloride;
[0030] The molar number j of Co in the cobalt source material and the molar number l of Na in the sodium source material satisfy: 0.5≤l / j≤1.0, preferably 0.6≤l / j≤0.9;
[0031] The M and the M' are both selected from at least one of Ni, Mn, Al, Mg, Co, Cu, Ca, Zn, Zr, B, Nb, Fe, Cr, Y, La, Ce, Cd or Al, and the M and the M' are the same metal element or different metal elements;
[0032] The molar number of M is p, the molar number of M' is q, and p, q and j satisfy: (p+q) / j=0.003-0.03.
[0033] Preferably, the high temperature calcination temperature is 700°C to 1000°C, preferably 800°C to 900°C, and the sintering time is 6 hours to 15 hours, preferably 8 hours to 12 hours;
[0034] The high-temperature calcination is carried out in an oxygen atmosphere, wherein the oxygen concentration is ≥ 90%.
[0035] Preferably, the molar concentration of the lithium compound in the lithium compound aqueous solution is greater than or equal to 2 mol / L, preferably greater than or equal to 2.5 mol / L; the lithium compound includes a first lithium compound and a second lithium compound; wherein the first lithium compound is lithium nitrate; the second lithium compound includes: one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium iodide, lithium fluoride, lithium bromide, and lithium phosphate;
[0036] The molar ratio of the added amount of the second lithium compound to the total added amount of the first lithium compound and the second lithium compound is N; wherein N=m(LiY) / n(LiY+Li NO3), m represents the molar content of the second lithium compound, n represents the sum of the molar contents of the first lithium compound and the second lithium compound, LiY represents the abbreviation of the second lithium compound, and 0.2≤N≤0.6.
[0037] Preferably, the molar ratio of Li / Na is greater than or equal to 5, preferably greater than or equal to 10; the temperature of the ion exchange is greater than or equal to 80°C, preferably greater than or equal to 90°C, and the time of the ion exchange is greater than or equal to 8 hours, preferably greater than or equal to 10 hours.
[0038] In a third aspect, an embodiment of the present invention provides an energy storage device, which contains the lithium cobalt oxide positive electrode material described in the first aspect or the lithium cobalt oxide positive electrode material obtained by the preparation method of the second aspect; the energy storage device is a lithium battery or a battery cell composed of lithium batteries.
[0039] The embodiment of the present invention provides a lithium cobalt oxide positive electrode material with an O2 phase structure and a preparation method and application thereof.
[0040] It has the following technical effects:
[0041] (1) A method for preparing a lithium cobalt oxide positive electrode material with an O2 phase structure provided in an embodiment of the present invention, by selecting a cobalt source material with specific parameters, calcining in an oxygen atmosphere, limiting the type of lithium compound and controlling the molar ratio of Li / Na, finally obtains a lithium cobalt oxide positive electrode material with a specific diffraction characteristic peak and a pure phase P63mc structure in the space group.
[0042] Specifically, first, a cobalt source material with a particle size and specific surface area tap density within an appropriate range is selected, and the molar number j of Co in the cobalt source material and the molar number l of Na in the sodium source material are limited to satisfy 0.5≤l / j≤1.0, so that the selected cobalt source material has very excellent ion diffusion performance when preparing the lithium cobalt oxide positive electrode material, which can ensure the subsequent synthesis of the lithium cobalt oxide positive electrode material with a higher space group purity.
[0043] Secondly, the cobalt source material, the sodium source material, the M element-containing material and the M' element-containing material are uniformly mixed in proportion and then calcined at high temperature to obtain an intermediate product. The calcination is carried out in an oxygen atmosphere, which can make the cobalt source material, the sodium source material, the M element-containing material and the M' element-containing material fully react to ensure the subsequent synthesis of lithium cobalt oxide positive electrode materials with higher element purity.
[0044] Then, a lithium compound aqueous solution capable of forming a eutectic phase is prepared, wherein there are two lithium compounds in the lithium compound aqueous solution, the first lithium compound is LiNO3, and the second lithium compound is collectively referred to as LiY, wherein the molar ratio of the amount of the second lithium compound added to the total amount of the first lithium compound and the second lithium compound added is N, and the range of N is limited to 0.2≤N≤0.6; the second lithium compound can form a eutectic phase with LiNO3 to affect the low eutectic point and promote subsequent ion exchange; by limiting the N value to the range of 0.2≤N≤0.6, the eutectic melting ratio of the two lithium compounds can be achieved, and since the eutectic temperature is lower than the melting points of the two lithium compound components, melting can be achieved at a lower temperature, thereby ensuring a higher ion concentration at a lower temperature, promoting rapid ion migration and exchange, and improving the kinetics of the ion exchange process, thereby obtaining a purer P63mc structure.
[0045] Finally, the intermediate product is weighed according to the molar ratio of lithium in the lithium compound aqueous solution to sodium in the intermediate product (Li / Na) being greater than or equal to 5, and added to the lithium compound aqueous solution for ion exchange. By controlling the temperature and time of the ion exchange, a lithium cobalt oxide positive electrode material with a pure phase P63mc structure with a relatively perfect lattice is obtained.
[0046] (2) The lithium cobalt oxide positive electrode material with an O2 phase structure prepared by the preparation method provided in the embodiment of the present invention has a pure phase P63mc space group structure, and the chemical formula is: Li 1+a (Co c M d ) (1+a) / (1+a+b) O2·X b (Co c M ’ d ) b / (1+a+b) O2, wherein -1<a≤0.1, 0<b≤1, 0<c≤1, 0≤d≤0.5, -1<a+b≤1.1, X comprises one or more elements selected from Na, K, Rb, Cs or B, and M and M' are selected from at least one element selected from Ni, Mn, Al, Mg, Co, Cu, Ca, Zn, Zr, B, Nb, Fe, Cr, Y, La, Ce, Cd or Al; the lithium cobalt oxide positive electrode material has a diffraction angle of 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0-16.5°, and there are characteristic diffraction peaks at the same time, which fully demonstrates the pure phase structure of the present invention.
[0047] In particular, at 2θ A1 and 2θ B1The peak intensities of the characteristic diffraction peaks at A1 and I B1 , I A1 ,I B1 The molar ratio of the amount of the second lithium compound added to the total amount of the first lithium compound and the second lithium compound added is N, which satisfies the relationship k·(I A1 / I B1 )=2.393-(N-0.4) 2 , where k is a correction coefficient, 0.9≤k≤1.1, 0.2≤N≤0.6. There are XRD diffraction characteristic peaks at the aforementioned diffraction angle positions and they conform to the above relationship, indicating that the lithium cobalt oxide positive electrode material of the present invention has a pure phase P63mc structure and has very good structural characteristics.
[0048] The lithium cobalt oxide positive electrode material provided in the embodiment of the present invention can effectively improve the charge transfer path and ion diffusion performance in the lithium cobalt oxide positive electrode material due to the above-mentioned special diffraction peak and the pure phase P63mc space group structure, so that the material has higher energy density, better rate performance and cycle performance under high voltage. Compared with traditional lithium cobalt oxide materials, the lithium cobalt oxide positive electrode material provided in the embodiment of the present invention has better structural stability and less lattice change, so it is less likely to have lattice fatigue during the cyclic charge and discharge process under high voltage, showing better cycle stability. It should be noted that although the lithium cobalt oxide positive electrode material of the present invention also improves the material cycle life by doping, its unique structure still allows the material to have better capacity performance, and the capacity of the material will not be reduced due to doping.
[0049] (3) The lithium cobalt oxide positive electrode material provided in the embodiment of the present invention is used in an energy storage device, such as a lithium battery or a battery cell composed of a lithium battery. Since the crystal structure of the lithium cobalt oxide positive electrode material of the present invention changes little, it has better thermal stability and safety when used as a battery positive electrode material, and can greatly reduce the risk of thermal runaway of the battery, thereby effectively improving the safety performance of the battery. In addition, the structure of the lithium cobalt oxide positive electrode material of the present invention is stable and can be applied to higher charging voltages, such as above 4.6V, thereby further improving the energy density of the material, and having better endurance and output performance when applied to batteries. The lithium-ion button half-cell prepared from the lithium cobalt oxide positive electrode material provided in the embodiment of the present invention has a first-week discharge specific capacity of ≥210.0 mAh / g at 0.1C, a first-week discharge specific capacity of ≥178 mAh / g at 0.5C, and a first-week discharge specific capacity of ≥167 mAh / g at 1.0C; the capacity retention rate after 100 cycles at 0.5C is approximately >97.5%; the lithium cobalt oxide prepared by the present invention has a capacity about 8 mAh / g to 12 mAh / g higher than that of traditional lithium cobalt oxide materials at 0.5C, and the cycle retention rate is improved by about 45% to 50%. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 A flow chart of a method for preparing a lithium cobalt oxide positive electrode material provided in an embodiment of the present invention.
[0051] Figure 2 The X-ray diffraction (XRD) spectra of the lithium cobalt oxide positive electrode material of Example 1 of the present invention and the lithium cobalt oxide material of Comparative Example 1 are shown.
[0052] Figure 3 The scanning electron microscope (SEM) images of the lithium cobalt oxide positive electrode material of Example 1 of the present invention and the lithium cobalt oxide material of Comparative Example 1 are shown.
[0053] Figure 4 Initial charge and discharge curves of button cells assembled in Example 1 and Comparative Example 1 at 0.1C.
[0054] Figure 5 The second week charge and discharge curves of the button cells assembled in Example 1 and Comparative Example 1 at 0.1C.
[0055] Figure 6 Capacity and capacity retention rate of button cells assembled from Example 1 and Comparative Example 1 after 100 cycles at 0.5C.
[0056] Figure 7 This is a rate performance diagram of button cells assembled in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0059] In order to facilitate a better understanding of the present invention, some technical terms are explained below.
[0060] The technical term "primary flake particle" refers to a single independent particle in the form of a flake.
[0061] The technical term "secondary single-crystal-like particles" refers to hard agglomerated particles formed by agglomeration of primary flake particles.
[0062] The technical term "median particle size D50" refers to the particle size corresponding to the cumulative value of the volume distribution of a sample in the secondary particles is 50%.
[0063] The technical term "eutectic point" is a kinetic term, which means that in some binary systems, during the heating process, the two components can melt into a liquid phase in any proportion. If the two components are mixed in an appropriate proportion, the two solid components can melt at the same time at a certain temperature, and this temperature is usually lower than the melting point of each pure component. This temperature is called the eutectic temperature. The point determined by the eutectic temperature and the eutectic components is called the eutectic point.
[0064] The technical terms "first charge specific capacity" and "first discharge specific capacity" refer to the charge specific capacity and discharge specific capacity of the first cycle respectively.
[0065] The technical term "activation" refers to the first cycle at 0.1C.
[0066] The technical term "initial discharge specific capacity" refers to the next discharge specific capacity after "activation", that is, the second week discharge specific capacity at 0.1C.
[0067] Next, based on the understanding of the above technical terms, the technical solution of the present invention is further described in detail through drawings and embodiments.
[0068] Studies have shown that by regulating the crystal structure, lattice parameters and crystal defects of lithium cobalt oxide, its charge transfer path and ion diffusion performance can be optimized, so the cycle stability of lithium cobalt oxide materials, especially the cycle stability under high voltage, can be further improved. The inventors found that the regulation of the crystal structure can help obtain lithium cobalt oxide positive electrode materials with excellent cycle stability, safety and high energy density. Therefore, further in-depth research on the crystal structure of lithium cobalt oxide materials is of great significance for further improving the electrochemical performance of lithium-ion batteries, solving safety problems and promoting the development of the new energy industry.
[0069] The embodiment of the present invention provides a lithium cobalt oxide positive electrode material with an O2 phase structure, and the chemical formula is: Li 1+a (Co c M d ) (1+a) / (1+a+b) O2·X b (Co c M ’ d ) b / (1+a+b)O2, wherein -1<a≤0.1, 0<b≤1, 0<c≤1, 0≤d≤0.5, -1<a+b≤1.1, X includes one or more elements selected from Na, K, Rb, Cs or B, and M and M' are both selected from at least one element selected from Ni, Mn, Al, Mg, Co, Cu, Ca, Zn, Zr, B, Nb, Fe, Cr, Y, La, Ce, Cd or Al.
[0070] The space group of the lithium cobalt oxide positive electrode material provided in the embodiment of the present invention is P63mc. The lithium cobalt oxide positive electrode material with a P63mc structure can effectively improve the charge transfer path and ion diffusion performance in the lithium cobalt oxide positive electrode material, and has better electrochemical performance than traditional lithium cobalt oxide materials.
[0071] The lithium cobalt oxide positive electrode material provided by the embodiment of the present invention is subjected to X-ray testing by a Co-Kα target material, and the diffraction angle is 2θ. A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0-16.5°, the diffraction characteristic peaks exist simultaneously. A1 The peak intensity of the characteristic diffraction peak at is set to I A1 , in 2θ B1 The peak intensity of the characteristic diffraction peak at is set to I B1 .
[0072] The lithium element in the lithium cobalt oxide positive electrode material comes from lithium compounds. The lithium compound includes a first lithium compound and a second lithium compound; wherein the first lithium compound is lithium nitrate; the second lithium compound includes: one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium iodide, lithium fluoride, lithium bromide, and lithium phosphate. The molar ratio of the amount of the second lithium compound added to the total amount of the first lithium compound and the second lithium compound added is N; wherein N = m(LiY) / n(LiY+LiNO3), m represents the molar content of the second lithium compound, n represents the sum of the molar contents of the first lithium compound and the second lithium compound, LiY represents the abbreviation of the second lithium compound, and 0.2≤N≤0.6.
[0073] Above I A1 ,I B1 and N satisfy the following relationship:
[0074] k·(I A1 / I B1 )=2.393-(N-0.4) 2, where k is a correction factor, 0.9≤k≤1.1. By limiting the N value to the above range, the present invention can reduce the temperature required for ion exchange, improve the kinetics of the ion exchange process, and obtain a more pure phase P63mc structure, which is manifested as lithium cobalt oxide at 2θ A1 The diffraction characteristic peak intensity I A1 , in 2θ B1 The diffraction characteristic peak intensity I B1 The ratio is within the optimal numerical range. At this time, the lithium cobalt oxide positive electrode material has a purer P63mc structural phase, and the lithium cobalt oxide positive electrode material has a higher specific capacity, better rate performance and cycle performance.
[0075] The morphology of the lithium cobalt oxide positive electrode material provided in the embodiment of the present invention is a secondary single crystal particle; the secondary single crystal particle is formed by a plurality of primary flaky particles; the thickness of the primary flaky particles is between 0.7 μm and 3.7 μm, and can be any value within the above range, such as 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3.0 μm, 3.5 μm, 3.7 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The thickness of the primary flaky particles of the lithium cobalt oxide positive electrode material provided in the embodiment of the present invention is obtained by scanning electron microscopy.
[0076] The median particle size D50 of the secondary single crystal particles of the lithium cobalt oxide positive electrode material is 2μm to 18μm, and can be any value within the above range, such as 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 12μm, 14μm, 16μm, 17μm, 18μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The median particle size of the secondary single crystal particles of the lithium cobalt oxide positive electrode material is obtained by testing with a laser particle size analyzer, and the median particle size D50 is preferably 4μm to 15μm.
[0077] The specific surface area of lithium cobalt oxide positive electrode material is 0.5m 2 / g~1.0m 2 / g, can be any value within the above range, such as 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g, etc., but are not limited to the listed values, and other values not listed in the numerical range are also applicable. The specific surface area is obtained by surface area meter testing. The preferred range of the specific surface area of lithium cobalt oxide positive electrode material is 0.6m 2 / g~0.9m 2 / g.
[0078] The true density of lithium cobalt oxide positive electrode material is 2g / cm 3 ~6g / cm 3 , can be any value within the above range, such as 2g / cm 3 , 3g / cm 3 , 4g / cm 3 , 5g / cm 3 , 6g / cm 3 etc., but are not limited to the listed values, and other values not listed in the numerical range are also applicable. The true density is obtained by a fully automatic true density analyzer through a gas replacement method. The preferred range of the true density of the lithium cobalt oxide positive electrode material is 3g / cm 3 ~5g / cm 3 .
[0079] Based on the weight of the unit lithium cobalt oxide positive electrode material, the residual alkali on the surface is 0.5% to 2.5%, which can be any value within the above range, such as 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.5%, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable. The residual alkali is measured by potentiometric titration, and the preferred range is 1% to 2%.
[0080] Based on the weight of the unit lithium cobalt oxide positive electrode material, the free sodium content is 0.5% to 2.5%, which can be any value within the above range, such as 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.5%, 1.6%, 1.8%, 2.0%, 2.5%, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable. Free sodium is measured by potentiometric titration, preferably 0.6% to 1.5%.
[0081] The present invention provides a method for preparing the lithium cobalt oxide positive electrode material. Figure 1 As shown, the specific steps include:
[0082] Step S1, uniformly mixing the cobalt source material, the sodium source material, the M element-containing material and the M' element-containing material according to a certain proportion to obtain a mixed material.
[0083] There is no particular limitation on the source of the cobalt source material, and the cobalt source material can be a commercially available product or a homemade one. As long as the cobalt source material has the structural features defined in the present invention, it is sufficient. In order to further ensure and improve the electrochemical performance of the lithium cobalt oxide positive electrode material, preferably, the cobalt source material of the present invention has the following characteristics:
[0084] The cobalt source material may be one or more of cobalt oxide, cobalt hydroxide, and cobalt salt, for example, may be selected from one or more of cobalt oxide, cobaltous oxide, cobalt tetroxide, cobalt chloride, cobalt sulfate, cobalt hydroxide, cobalt oxalate, cobalt carbonate, and organic acid cobalt; in addition, the cobalt source material may also be a doped cobalt source, for example, cobalt oxide, cobalt hydroxide, and cobalt salt doped with M and / or M', where M and M' include but are not limited to one or more elements of Ni, Mn, Al, Mg, Co, Cu, Ca, Zn, Zr, B, Nb, Fe, Cr, Y, La, Ce, Cd, and Al.
[0085] The median particle size D50 of the cobalt source material is 1μm to 20μm, and can be any value within the above range, such as 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 12μm, 14μm, 16μm, 17μm, 18μm, 19μm, 20μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0086] The specific surface area of the cobalt source material is 2.5m 2 / g~5.5m 2 / g, can be any value within the above range, such as 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0087] The tap density of the cobalt source material is 2.0g / cm 3 ~3.2g / cm 3 , can be any value within the above range, such as 2.0 g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , 2.8g / cm 3 、3.0g / cm 3、3.2g / cm 3 The above values are not limited to the above listed values, and other values not listed in the above listed values are also applicable.
[0088] When the cobalt source material meets the range defined by the above parameters, the cobalt source material has a higher reaction activity. When it is used to prepare lithium cobalt oxide positive electrode materials, it has very excellent ion diffusion performance, which can ensure the synthesis of lithium cobalt oxide positive electrode materials with higher purity.
[0089] The sodium source material includes one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium nitrate, sodium oxide, sodium peroxide, sodium sulfate, and sodium chloride.
[0090] M in the M-element material and M' in the M'-element material are both selected from oxides, hydroxides, fluorides, inorganic salts, and organic salt compounds of at least one element selected from Ni, Mn, Al, Mg, Co, Cu, Ca, Zn, Zr, B, Nb, Fe, Cr, Y, La, Ce, Cd, or Al; M and M' are the same metal element or different metal elements.
[0091] The molar number j of Co in the cobalt source material and the molar number l of Na in the sodium source material satisfy: 0.5≤l / j≤1.0, l / j can be any value within the above range, such as 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable; the preferred range of l / j is 0.6≤l / j≤0.9.
[0092] The mixture after the two materials are mixed is a sodium cobaltate material. When the initial feed range before mixing is large, the sodium cobaltate material with a pure phase structure can only be formed with a fixed stoichiometric ratio (for example, l / j=0.67, 0.83). For the above molar ratio of sodium element and cobalt element, it can be ensured that P2 type pure phase sodium cobaltate is fully generated in step S1.
[0093] The molar number of the M element is set to p, and the molar number of the M' element is set to q, wherein p, q and j satisfy: (p+q) / j=0.003-0.03.
[0094] In step S1, there is no requirement for the mixing time and mixing intensity, as long as there are no obvious sodium carbonate agglomeration white spots in the mixed material.
[0095] Step S2, calcining the mixed material at high temperature to obtain an intermediate product.
[0096] Among them, the temperature of high-temperature calcination is between 700°C and 1000°C, and can be any value within the above range, such as 700°C, 800°C, 900°C, 1000°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable; the preferred range of high-temperature calcination temperature is 800°C to 900°C.
[0097] The sintering time of high temperature calcination is 6 hours to 15 hours, which can be any value within the above range, such as 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The sintering time of high temperature calcination is preferably 8 hours to 12 hours.
[0098] The high temperature calcination is carried out in an oxygen atmosphere, wherein the oxygen concentration is ≥ 90%.
[0099] The present invention performs the calcination treatment under the above conditions, so that the obtained material particles have uniform and rounded sizes, providing favorable conditions for ion exchange.
[0100] Step S3, weigh a certain amount of lithium compound and dissolve it in pure water to obtain a lithium compound aqueous solution.
[0101] Wherein, the molar concentration of the lithium compound in the lithium compound aqueous solution is greater than or equal to 2 mol / L, preferably greater than or equal to 2.5 mol / L;
[0102] The lithium compound includes a first lithium compound and a second lithium compound; wherein the first lithium compound is lithium nitrate; the second lithium compound includes: one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium iodide, lithium fluoride, lithium bromide, and lithium phosphate; the second lithium compound can form a eutectic phase with lithium nitrate to affect the low eutectic point and promote ion exchange.
[0103] The molar ratio of the added amount of the second lithium compound to the total added amount of the first lithium compound and the second lithium compound is N; wherein N=m(LiY) / n(LiY+Li NO3), m represents the molar content of the second lithium compound, n represents the sum of the molar contents of the first lithium compound and the second lithium compound, LiY represents the abbreviation of the second lithium compound, and 0.2≤N≤0.6, the value of N can be any value within the above range, such as 0.2, 0.3, 0.4, 0.5, 0.6, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0104] The selection of lithium compounds in the present invention affects the rate, temperature and time of ion exchange. The value of the addition ratio N of the two lithium compounds affects the low eutectic point. The low eutectic point shows a rule of first decreasing and then increasing with the increase of N value. Therefore, a suitable N value can obtain a higher ion concentration at a lower temperature, promote rapid ion migration and exchange, and improve the kinetics of the ion exchange process, thereby obtaining a purer P63mc structure.
[0105] Step S4, weighing the intermediate product according to a certain Li / Na molar ratio, adding it to a lithium compound aqueous solution for ion exchange, and obtaining an ion exchange product;
[0106] Wherein, the molar ratio of lithium in the lithium complex aqueous solution to sodium in the intermediate product (Li / Na) is greater than or equal to 5, and the molar ratio can be any value within the above range, such as 5, 6, 7, 8, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The molar ratio of Li / Na is preferably greater than or equal to 10.
[0107] The temperature of ion exchange in this step is greater than or equal to 80°C, and can be any temperature within the above range, such as 80°C, 90°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, etc., but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. The temperature of ion exchange is preferably greater than or equal to 90°C; the time of ion exchange is greater than or equal to 8 hours, such as 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, etc., but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. The time of ion exchange is preferably greater than or equal to 10 hours.
[0108] In this step, the temperature and time selected for ion exchange affect the formation and proportion of the lithium cobalt oxide crystal structure. Longer time and higher temperature will promote the ion exchange process, and more crystal structures will be formed.
[0109] Step S5, washing and drying the ion exchange product to obtain a lithium cobalt oxide positive electrode material.
[0110] The washing step is to use deionized water to wash the product after ion exchange, and the number of washing times is greater than or equal to 3 times, preferably 5 times.
[0111] The drying in this step is performed by vacuum drying, and the drying temperature is between 60° C. and 150° C., preferably in the range of 80° C. and 130° C. The drying time is greater than or equal to 4 hours.
[0112] The lithium cobalt oxide positive electrode material prepared by the above preparation method can be used as a positive electrode active material in an energy storage device, wherein the energy storage device is a lithium battery or a battery cell composed of lithium batteries.
[0113] The lithium-ion button half-cell assembled with the positive electrode sheet prepared from the above-mentioned lithium cobalt oxide positive electrode material provided in the embodiment of the present invention has a first-week discharge specific capacity of ≥210.0 mAh / g at 0.1C, a first-week discharge specific capacity of ≥178 mAh / g at 0.5C, and a first-week discharge specific capacity of ≥167 mAh / g at 1.0C; the capacity retention rate after 100 cycles at 0.5C is approximately >97.5%.
[0114] The lithium cobalt oxide positive electrode material prepared in the embodiment of the present invention has a higher capacity than the conventional lithium cobalt oxide at 0.5C by about 8 mAh / g to 12 mAh / g, and a cycle retention rate of about 45% to 50%. Compared with the existing O2-type lithium cobalt oxide, the lithium cobalt oxide positive electrode material provided in the embodiment of the present invention exhibits better rate performance and cycle stability.
[0115] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the lithium cobalt oxide positive electrode material of the present invention are respectively described below with multiple specific examples.
[0116] Example 1
[0117] This embodiment provides a preparation process of a lithium cobalt oxide positive electrode material. The chemical formula of the lithium cobalt oxide positive electrode material is Li 0.68 Co 0.958 Al 0.0136 O2·Na 0.02 Co 0.028 A l 0.0004 O2 (abbreviated as LCO-1), the specific preparation process is as follows.
[0118] (1) 100 g of cobalt oxide, sodium carbonate and titanium oxide were uniformly mixed in a molar ratio of Co:Na:Al of 0.986:0.7:0.014 to obtain a mixed material. The median particle size D50 of the cobalt oxide used was 5.5 μm and the specific surface area was 4.4 m 2 / g, tap density is 2.5g / cm 3 .
[0119] (2) placing the mixed material in a high temperature furnace, heating it to 900° C. at a heating rate of 5° C. / min in an oxygen atmosphere with an oxygen concentration of ≥90%, and calcining it at high temperature for 10 hours to obtain an intermediate product.
[0120] (3) According to the molar ratio N = m (Li OH) / n (Li OH + LiNO 3) = 0.4, Li OH and Li NO 3 were weighed respectively, and a certain amount of pure water was added to prepare a 2.5 mol / L aqueous solution of lithium compound to obtain a lithium compound aqueous solution.
[0121] (4) Weighing the intermediate product according to a Li / Na molar ratio of 10, adding it to a lithium compound aqueous solution for ion exchange, controlling the temperature during the ion exchange process to 90° C. and the ion exchange time to 10 hours, to obtain an ion exchange product.
[0122] (5) The ion exchange product was washed five times with deionized water and then dried at 100° C. to obtain a lithium cobalt oxide positive electrode material.
[0123] The XRD pattern of the lithium cobalt oxide positive electrode material prepared in this example is as follows: Figure 2 As shown, it can be seen that at 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 2.393, and the addition ratio N of the lithium compound satisfies the following relationship: k·(I A1 / I B1 )=2.393-(N-0.4) 2 , where k is 1.
[0124] The SEM image of the lithium cobalt oxide positive electrode material prepared in this example is as follows: Figure 3 Shown are images at 10 μm and 50 μm resolution, respectively.
[0125] Example 2
[0126] This embodiment provides a preparation process of a lithium cobalt oxide positive electrode material. The chemical formula of the lithium cobalt oxide positive electrode material is Li 0.65 Co 0.916 A l 0.013 O2·Na 0.05 Co 0.07 A l 0.001 O2 (abbreviated as LCO-2), the specific preparation process is as follows.
[0127] (1) The process is the same as in Example 1.
[0128] (2) The process is the same as in Example 1.
[0129] (3) According to the molar ratio N = m (Li OH) / n (Li OH + LiNO 3) = 0.3, Li OH and Li NO 3 were weighed respectively, and a certain amount of pure water was added to prepare a 2.5 mol / L aqueous solution of lithium compound to obtain a lithium compound aqueous solution.
[0130] (4) The process is the same as in Example 1.
[0131] (5) The process is the same as in Example 1 to obtain a lithium cobalt oxide positive electrode material.
[0132] The lithium cobalt oxide positive electrode material prepared in this example has a 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 2.390, and the addition ratio N of the lithium compound satisfies the following relationship: k·(I A1 / I B1 )=2.393-(N-0.4) 2 , where k is 0.997.
[0133] Example 3
[0134] This embodiment provides a preparation process of a lithium cobalt oxide positive electrode material. The chemical formula of the lithium cobalt oxide positive electrode material is Li 0.66 Co 0.930 A l 0.0132 O2·Na 0.04 Co 0.056 A l 0.0008 O2 (abbreviated as LCO-3), the specific preparation process is as follows.
[0135] (1) The process is the same as in Example 1.
[0136] (2) The process is the same as in Example 1.
[0137] (3) According to the molar ratio N = m (Li OH) / n (Li OH + LiNO 3) = 0.5, Li OH and Li NO 3 were weighed respectively, and a certain amount of pure water was added to prepare a 2.5 mol / L aqueous solution of lithium compound to obtain an aqueous solution of lithium compound.
[0138] (4) The process is the same as in Example 1.
[0139] (5) The process is the same as in Example 1 to obtain a lithium cobalt oxide positive electrode material.
[0140] The lithium cobalt oxide positive electrode material prepared in this example has a 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 2.388, and the addition ratio N of the lithium compound satisfies the following relationship: k·(I A1 / I B1 )=2.393-(N-0.4) 2 , where k is 0.998.
[0141] Example 4
[0142] This embodiment provides a preparation process of a lithium cobalt oxide positive electrode material. The chemical formula of the lithium cobalt oxide positive electrode material is Li 0.61 Co 0.859 A l 0.0122 O2·Na 0.09 Co 0.127 A l 0.0018 O2 (abbreviated as LCO-4), the specific preparation process is as follows.
[0143] (1) The process is the same as in Example 1.
[0144] (2) The process is the same as in Example 1.
[0145] (3) The process is the same as in Example 1.
[0146] (4) Weighing the intermediate product according to a Li / Na molar ratio of 5, adding it into a lithium compound aqueous solution for ion exchange, controlling the temperature during the ion exchange process to 90° C. and the ion exchange time to 10 hours, to obtain an ion exchange product.
[0147] (5) The process is the same as in Example 1 to obtain a lithium cobalt oxide positive electrode material.
[0148] The lithium cobalt oxide positive electrode material prepared in this example has a 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 2.382, and the addition ratio N of the lithium compound satisfies the following relationship: k·(I A1 / I B1 )=2.393-(N-0.4) 2 , where k is 1.005.
[0149] Example 5
[0150] This embodiment provides a preparation process of a lithium cobalt oxide positive electrode material. The chemical formula of the lithium cobalt oxide positive electrode material is Li 0.63 Co 0.887 A l 0.0126 O2·Na 0.07 Co 0.099 A l 0.0014 O2 (abbreviated as LCO-5), the specific preparation process is as follows.
[0151] (1) The process is the same as in Example 1.
[0152] (2) The process is the same as in Example 1.
[0153] (3) According to the molar ratio N = m (Li OH) / n (Li OH + LiNO 3) = 0.4, Li OH and Li NO 3 were weighed respectively, and a certain amount of pure water was added to prepare a 2.0 mol / L aqueous solution of lithium compound to obtain an aqueous solution of lithium compound.
[0154] (4) The process is the same as in Example 1.
[0155] (5) The process is the same as in Example 1 to obtain a lithium cobalt oxide positive electrode material.
[0156] The lithium cobalt oxide positive electrode material prepared in this example has a 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 2.385, and the addition ratio N of the lithium compound satisfies the following relationship: k·(I A1 / I B1 )=2.393-(N-0.4) 2 , where k is 1.003.
[0157] Example 6
[0158] This embodiment provides a preparation process of a lithium cobalt oxide positive electrode material. The chemical formula of the lithium cobalt oxide positive electrode material is Li 0.65 Co 0.916 A l 0.013 O2·Na0.05 Co 0.07 A l 0.001 O2 (abbreviated as LCO-6), the specific preparation process is as follows.
[0159] (1) The process is the same as in Example 1.
[0160] (2) The process is the same as in Example 1.
[0161] (3) The process is the same as in Example 1.
[0162] (4) Weighing the intermediate product according to a Li / Na molar ratio of 10, adding it to a lithium compound aqueous solution for ion exchange, controlling the temperature during the ion exchange process to 80° C. and the ion exchange time to 10 hours, to obtain an ion exchange product.
[0163] (5) The process is the same as in Example 1 to obtain a lithium cobalt oxide positive electrode material.
[0164] The lithium cobalt oxide positive electrode material prepared in this example has a 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 2.388, and the addition ratio N of the lithium compound satisfies the following relationship: k·(I A1 / I B1 )=2.393-(N-0.4) 2 , where k is 1.002.
[0165] Example 7
[0166] This embodiment provides a preparation process of a lithium cobalt oxide positive electrode material. The chemical formula of the lithium cobalt oxide positive electrode material is Li 0.64 Co 0.901 A l 0.0128 O2·Na 0.06 Co 0.085 A l 0.0012 O2 (abbreviated as LCO-7), the specific preparation process is as follows.
[0167] (1) The process is the same as in Example 1.
[0168] (2) The process is the same as in Example 1.
[0169] (3) The process is the same as in Example 1.
[0170] (4) Weighing the intermediate product according to a Li / Na molar ratio of 10, adding it into a lithium compound aqueous solution for ion exchange, controlling the temperature during the ion exchange process to 90° C. and the ion exchange time to 8 hours, to obtain an ion exchange product.
[0171] (5) The process is the same as in Example 1 to obtain a lithium cobalt oxide positive electrode material.
[0172] The lithium cobalt oxide positive electrode material prepared in this example has a 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 2.383, and the addition ratio N of the lithium compound satisfies the following relationship: k·(I A1 / I B1 )=2.393-(N-0.4) 2 , where k is 1.004.
[0173] Example 8
[0174] This embodiment provides a preparation process of a lithium cobalt oxide positive electrode material. The chemical formula of the lithium cobalt oxide positive electrode material is Li 0.68 Co 0.958 Al 0.0136 O2·Na 0.02 Co 0.028 T i 0.0004 O2 (abbreviated as LCO-8), the specific preparation process is as follows.
[0175] (1) Cobalt oxide, sodium carbonate and titanium oxide were mixed in a molar ratio of Co:Na:Al:Ti of 0.986:
[0176] 0.7:0.0136:0.0004 Take a total of 100 grams, mix them evenly, and obtain a mixed material.
[0177] (2) The process is the same as in Example 1.
[0178] (3) The process is the same as in Example 1.
[0179] (4) The process is the same as in Example 1.
[0180] (5) The process is the same as in Example 1.
[0181] The lithium cobalt oxide positive electrode material prepared in this example has a 2θ A1 =18.3~18.9°, 2θA2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 2.394, and the addition ratio N of the lithium compound satisfies the following relationship: k·(I A1 / I B1 )=2.393-(N-0.4) 2 , where k is 0.9996.
[0182] In order to better illustrate the effect of the embodiment of the present invention, a comparative example is compared with the above embodiment.
[0183] Comparative Example 1
[0184] This comparative example uses conventional lithium cobalt oxide sold on the market, and its chemical formula is
[0185] L i 1.03 Co 0.986 A l 0.014 O2, named LCO-D1.
[0186] The XRD pattern of the commonly used lithium cobalt oxide is as follows: Figure 2 As shown, it can be seen that at 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 There is no XRD diffraction characteristic peak at =16.0~16.5°.
[0187] The SEM image of the conventional lithium cobalt oxide is shown in Figure 3 As shown, it can be seen that the images at a resolution of 10 μm and 50 μm respectively show that the morphology of the lithium cobalt oxide positive electrode material prepared in Example 1 is different.
[0188] Comparative Example 2
[0189] This comparative example prepares a lithium cobalt oxide material having the chemical formula
[0190] L i 0.55 Co 0.775 A l 0.011 O2·Na 0.15 Co 0.211 A l 0.003O2 (abbreviated as LCO-D2), the preparation process is different from that of Example 1 in that in step (3), LiOH and LiNO3 are weighed separately according to the molar ratio N=m(LiOH) / n(LiOH+LiNO3)=0.1, and a certain amount of pure water is added to prepare a 2.5 mol / L aqueous solution of a lithium compound to obtain a lithium compound aqueous solution. The other steps are the same as those of Example 1.
[0191] The lithium cobalt oxide material prepared in this comparative example has a 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 0.611, but the peak intensity and the lithium compound addition ratio N do not satisfy the relationship k·(I A1 / I B1 )=2.393-(N-0.4) 2 (When 0.9≤k≤1.1).
[0192] Comparative Example 3
[0193] This comparative example prepares a lithium cobalt oxide material having the chemical formula
[0194] L i 0.05 Co 0.07 A l 0.001 O2·Na 0.65 Co 0.916 A l 0.013 O2 (abbreviated as LCO-D3), the preparation process is different from that of Example 1 in that in step (3), LiOH and LiNO3 are weighed separately according to the molar ratio N=m(LiOH) / n(LiOH+LiNO3)=0.7, and a certain amount of pure water is added to prepare a 2.5 mol / L aqueous solution of a lithium compound to obtain a lithium compound aqueous solution. The other steps are the same as those of Example 1.
[0195] The lithium cobalt oxide material prepared in this comparative example has a 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 0.721, but the peak intensity and the lithium compound addition ratio N do not satisfy the relationship k·(I A1 / IB1 )=2.393-(N-0.4) 2 (When 0.9≤k≤1.1).
[0196] Comparative Example 4
[0197] This comparative example prepares lithium cobalt oxide material, the chemical formula of which is Na 0.7 Co 0.986 A l 0.014 O2 (abbreviated as LCO-D4), the preparation process is different from that of Example 1 in that in step (3), Li2CO3 and Li NO3 are weighed separately according to the molar ratio N=m(Li2CO3) / n(Li2CO3+Li NO3)=0.7, and a certain amount of pure water is added to prepare a 2.5 mol / L aqueous solution of a lithium compound to obtain a lithium compound aqueous solution. The other steps are the same as those of Example 1.
[0198] The lithium cobalt oxide material prepared in this comparative example has only B1 =16.0~16.5° and there are characteristic XRD diffraction peaks.
[0199] Comparative Example 5
[0200] This comparative example prepares a lithium cobalt oxide material having the chemical formula
[0201] L i 0.33 Co 0.465 A l 0.0066 O2·Na 0.37 Co 0.521 A l 0.0074 O2 (abbreviated as LCO-D5), the preparation process is different from that of Example 1 in that step (4) the intermediate product is weighed according to the Li / Na molar ratio equal to 1, added to the lithium compound aqueous solution for ion exchange, the temperature during the ion exchange process is controlled to be 90°C, the ion exchange time is 10 hours, and the ion exchange product is obtained. The other steps are the same as those of Example 1.
[0202] The lithium cobalt oxide material prepared in this comparative example has a 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 1.586, but the peak intensity and the lithium compound addition ratio N do not satisfy the relationship k·(I A1 / I B1 )=2.393-(N-0.4) 2(When 0.9≤k≤1.1).
[0203] Comparative Example 6
[0204] This comparative example prepares a lithium cobalt oxide material having the chemical formula
[0205] L i 0.28 Co 0.394 A l 0.0056 O2·Na 0.42 Co 0.592 A l 0.0084 O2 (abbreviated as LCO-D6), the preparation process is different from that of Example 1 in that in step (3), LiOH and LiNO3 are weighed separately according to the molar ratio N=m(LiOH) / n(Li OH+LiNO3)=0.4, and a certain amount of pure water is added to prepare a 1 mol / L aqueous solution of a lithium compound to obtain a lithium compound aqueous solution. The other steps are the same as those of Example 1.
[0206] The lithium cobalt oxide material prepared in this comparative example has a 2θ A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 1.806, but the peak intensity and the lithium compound addition ratio N do not satisfy the relationship k·(I A1 / I B1 )=2.393-(N-0.4) 2 (When 0.9≤k≤1.1).
[0207] The above embodiments and comparative examples were subjected to physical and chemical index analysis and testing, and the test items and methods are as follows:
[0208] The materials of Examples 1-8 and Comparative Examples 1-6 were tested for element content, median particle size, true density, specific surface area, residual alkali and free sodium, compacted density, primary flake particle size and XRD.
[0209] Element content test: tested by Agilent 5800I CP-OES spectrometer, the argon partial pressure gauge is controlled at 80psi-100psi, the liquid argon booster valve compression control pressure is above 200psi, nitrogen is 60psi-100psi, compressed air is 80psi-100psi; when making the standard curve, a three-point calibration is required according to the concentration of the sample, and the coefficient of the standard curve is above 0.9999.
[0210] Median particle size test: Malvern laser particle size analyzer Mastersize 3000 was used for the test. A certain amount of sodium pyrophosphate dispersant was added and the sample was added to a light shielding range of 10%-20%. Ultrasonication was performed for 3 minutes before starting the test. The average of three tests was taken as the median particle size measurement value.
[0211] True density test: The test was conducted by gas replacement method using BSD-TD-K fully automatic true density analyzer. The sample was dried at 110°C and the vacuum pumping time was 15-20 minutes until the vacuum degree reached 750 mmhg. The average value was taken after 5 parallel tests.
[0212] Specific surface area test: The specific surface area tester of Tristar II 3020 produced by American MicromerAlcs Company was used for the test, and the degassing temperature was set to 300°C and the degassing time was set to 120 min.
[0213] Residual alkali and free sodium test: Determined by potentiometric titration, the reagents used are all high-grade pure reagents and first-grade water in accordance with GB / T6682. Stir and mix at 800r / min for 5 minutes, titrate with 0.1mol / L hydrochloric acid standard titration solution, calibrate the pH electrode of the potentiometric titrator before titration, and use pH standard buffer for three-point calibration, with the slope in the range of 0.95 to 1.05.
[0214] Compaction density test: It is measured using the MCP-PD51 compaction density meter produced by Mitsubishi Chemical of Japan. 1±0.01g of sample is weighed and the pressure of 3T is selected for testing.
[0215] Primary particle flake particle size test: Use S-4800 scanning electron microscope of Hitachi HI TACH I of Japan for testing, with test voltage of 1kV-5kV and test magnification of 1k-30k.
[0216] XRD test: The XRD-6000 X-ray powder diffractometer produced by Shimadzu of Japan was used for the test. The voltage was set to 40 kV, the current to 40 mA, the step length to 0.005°, the height limit slit to 10 mm, the divergence slit to 1 / 2°, the anti-scattering slit to 8 mm, the receiving slit to open, the test scanning 2θ angle to 10° to 80°, the continuous scanning in 1D mode, and the scanning speed to 1.2° / min.
[0217] Table 1 is a summary of the physical and chemical index tests of materials in Examples 1-8 and Comparative Examples 1-6.
[0218]
[0219] Table 1
[0220] It can be seen from the test data in Table 1 that the median particle size D50 of the secondary particles of the lithium cobalt oxide positive electrode materials of Examples 1-8 of the present invention is in the range of 4.8 μm to 5.6 μm, and the specific surface area is in the range of 0.78 m 2 / g~0.83m 2 / g range, the true density is 4.75g / cm 3 ~4.88g / cm 3 The residual alkali content is in the range of 1.02% to 1.22%, the free sodium content is in the range of 0.81% to 0.90%, the primary particles are in the flaky morphology, and the particle size is between 1.71μm and 1.77μm. The XRD characteristic peak I A1 / I B1 Satisfy k·(I A1 / I B1 )=2.393-(N-0.4) 2 .
[0221] The median particle size D50 of the secondary particles of the materials of Comparative Examples 1-6 is in the range of 4.3 μm to 5.8 μm, and the specific surface area is in the range of 0.65 m 2 / g~0.88m 2 / g range, the true density is 4.68g / cm 3 ~4.96g / cm 3 The residual alkali content is in the range of 0.60% to 0.88%, the free sodium content is in the range of 0.01% to 1.40%, the particles of the materials in Comparative Examples 2, 5, and 6 are flaky in shape, and the particle size is in the range of 0.58μm to 0.64μm, and the other comparative materials are not flaky in shape. The XRD test results show that no characteristic peak of the O2 phase structure is found in Comparative Example 1, no characteristic peak of A1 is found in Comparative Example 4, and I A1 / I B1 Does not satisfy k·(I A1 / I B1 )=2.393-(N-0.4) 2 .
[0222] The materials of the above-mentioned embodiments and comparative examples were used to prepare button-type half-cells and conduct electrochemical performance tests. The battery assembly and testing process is as follows:
[0223] The preparation steps of button half-cell are as follows: lithium cobalt oxide, conductive carbon black and polyvinylidene fluoride are mixed into a uniform slurry at a mass ratio of 96:2:2 using N-methylpyrrolidone as solvent, and then the slurry is coated on a 10 μm thick aluminum foil with a surface loading of 14 mg / cm 2After drying, it was cut into a circular positive electrode sheet with a diameter of 12 mm. The prepared circular electrode sheet was used as the positive electrode, lithium metal as the negative electrode, and the diaphragm was a PE diaphragm coated with aluminum oxide on both sides. The electrolyte of 1 mol / L Li PF6 dissolved in EC:DMC=1:1 solvent was selected to assemble the R2032 button half-cell, and the injection volume was 60 μL.
[0224] Use the charge and discharge tester to test the assembled R2032 button half-cell. The steps are as follows:
[0225] (1) Capacity test at 25°C: Place the button half-cell in a constant temperature box at 25°C. Set the current density to 27.4 mA / g (0.1C) and the charge cut-off voltage to 4.6 V (vs Li + / Li), the discharge cut-off voltage is 3V (vs Li + / Li), two cycles.
[0226] (2) Cycling performance test at 25°C: The button half-cell was placed in a constant temperature box at 25°C. After two weeks of cycling in step 1), the current was reset to 137 mA / g (0.5C) and the charge cut-off voltage was 4.6 V (vs Li + / L i), discharge cut-off voltage is 3V (vs Li + / Li) for 100 cycles.
[0227] (3) Rate charge and discharge performance test at 25°C: The button half-cell was placed in a constant temperature box at 25°C. The charge cut-off voltage was 4.6V (vs Li + / L i), discharge cut-off voltage is 3V (vs L i + / L i). The cells were charged and discharged at constant currents of 27.4 mA / g (0.1C), 137 mA / g (0.5C), and 274 mA / g (1C), and the capacity of the first cycle was compared for 5 cycles at each current density.
[0228] The initial charge and discharge curves of the button-type half-cells assembled in Example 1 and Comparative Example 1 at 0.1C are as follows: Figure 4 As shown, it can be seen that the discharge specific capacity of the button-type half-cell assembled in Example 1 is significantly higher than that of the battery in Comparative Example 1.
[0229] The charge and discharge curves of the button-type half-cells assembled in Example 1 and Comparative Example 1 at 0.1C in the second week are as follows: Figure 5 As shown, it can be seen that the second week discharge specific capacity of the button-type half-cell assembled in Example 1 is significantly higher than that of the button-type half-cell in Comparative Example 1.
[0230] The capacity and capacity retention rate of the button-type half-cells assembled in Example 1 and Comparative Example 1 after 100 cycles at 0.5C are as follows: Figure 6 As shown, it can be seen that the button half-cell containing the lithium cobalt oxide positive electrode material of Example 1 has a much higher discharge capacity and cycle capacity retention rate at 0.5C for 100 cycles than the button half-cell containing the traditional lithium cobalt oxide material of Comparative Example 1.
[0231] The rate performance comparison chart of button-type half-cells assembled in Example 1 and Comparative Example 1 is as follows: Figure 7 As shown, it can be seen that the rate performance of the button-type half-cell of Example 1 is better than that of the button-type half-cell of Comparative Example 1.
[0232] The first-week discharge specific capacity, first-week coulomb efficiency, initial discharge specific capacity (second discharge specific capacity), rate performance, 100th discharge specific capacity at 0.5C, and 100th capacity retention rate measured for the batteries of Examples 1-8 and Comparative Examples 1-6 are summarized in Table 2.
[0233]
[0234]
[0235] Table 2
[0236] It can be seen from the test data in Table 2 that the first week discharge specific capacities of the button cells prepared from the lithium cobalt oxide positive electrode materials of Examples 1-8 at 0.1C are 214.0 mAh / g, 210.8 mAh / g, 211.5 mAh / g, 210.1 mAh / g, 210.2 mAh / g, 210.7 mAh / g, 210.6 mAh / g and 213.6 mAh / g, respectively. Each example has an excellent first week specific capacity, all higher than 210.0 mAh / g, and all better than the batteries assembled in Comparative Examples 1-6; the first week coulombic efficiency of the button cells of Examples 1-8 is The rates are 92.2%, 91.2%, 91.5%, 91.6%, 91.7%, 91.8%, 91.6%, 91.1%, and the coulombic efficiency of each embodiment exceeds 91%; the discharge capacity in the second week at 0.1C is 206.7mAh / g, 203.9mAh / g, 204.3mAh / g, 201.8mAh / g, 203.2mAh / g, 203.4mAh / g, 201.9mAh / g, 206.0mAh / g, and each embodiment has an excellent discharge capacity, all higher than 200.0mAh / g. It can be seen that the lithium cobalt oxide positive electrode material with O2 phase structure provided by the embodiment of the present invention has excellent specific capacity and can meet the battery's demand for high energy density.
[0237] The discharge specific capacities of button-type half-cells assembled in Examples 1-8 of the present invention at 0.5C are 183.2mAh / g, 180.4mAh / g, 181.8mAh / g, 179.4mAh / g, 178.8mAh / g, 181.0mAh / g, 179.6mAh / g, and 183.0mAh / g, respectively; the discharge specific capacities at 1C are 172.0mAh / g, 169.6mAh / g, 170.5mAh / g, 168.7mAh / g, 167.2mAh / g, 170.6mAh / g, 167.9mAh / g, and 171.4mAh / g, respectively. It can be seen that the lithium cobalt oxide positive electrode materials with O2 phase structure provided in the embodiments of the present invention all have good rate performance, and when the current density increases from 0.5C to 1C, they still have a specific capacity of more than 167mAh / g.
[0238] The discharge specific capacities of the batteries assembled in Examples 1-8 of the present invention after 100 cycles at 0.5C are 179.9mAh / g, 176.8mAh / g, 178.1mAh / g, 176.1mAh / g, 175.2mAh / g, 177.6mAh / g, 176.0mAh / g, and 178.5mAh / g, respectively; and the capacity retention rates after 100 cycles at 0.5C are approximately 98.20%, 98.00%, 97.96%, 98.16%, 97.99%, 98.12%, 98.00%, and 97.54%, respectively. It can be seen that when cycling in the voltage range of 3.0V-4.6V, the battery prepared by the lithium cobalt oxide positive electrode material with O2 phase structure provided in the embodiment of the present invention still has a high specific capacity after 100 cycles, and the capacity retention rate is also approximately greater than 97.5%, and has very good cycle stability under high voltage.
[0239] The electrochemical performance parameters of Examples 1-8 show that the positive electrode material in Example 1 is the best in terms of the first discharge capacity at 0.1C, the second week discharge capacity at 0.1C, the discharge capacity at 0.5C, the discharge capacity at 1C, the discharge capacity after 100 cycles at 0.5C, and the capacity retention rate. The chemical formula of the lithium cobalt oxide positive electrode material in Example 1 is Li 0.68 Co 0.958 A l 0.0136 O2·Na 0.02 Co 0.028 A l 0.0004 O2, the molar ratio of Co in the cobalt source material to Na in the sodium source material is l(Na):j(Co)=0.7:0.986, and the lithium compound is calculated according to m(LiOH)
[0240] / n(LiOH+LiNO3)=0.4LiOH and LiNO3 were weighed and prepared into a 2.5 mol / L aqueous solution, and ion exchange was performed according to a Li / Na molar ratio of 10. The temperature during the ion exchange process was 90°C and the time was 10 hours. The median particle size D50 of the secondary particles of the lithium cobalt oxide positive electrode material obtained by the above process was 5.6 μm, and the specific surface area was 0.78 m 2 / g, true density is 4.88g / cm 3 The residual alkali content is 1.15%, the free sodium content is 0.81%, the primary particles are flake-like in morphology, and the particle size is 1.77 μm. A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 =16.0~16.5°There is a characteristic XRD diffraction peak, and the peak intensity is higher than I A1 / I B1 is 2.393, and the addition ratio N of the lithium compound satisfies the following relationship: k·(I A1 / I B1 )=2.393-(N-0.4) 2 , where k is 1. It can be seen that in Example 1, the N value is limited to 0.4 to ensure that the composite lithium compound has a suitable melting point, the ratio of the cobalt source material and the sodium source material is limited to l(Na) / j(Co) of about 0.7 to ensure that a pure phase P2 type precursor is obtained, the Li / Na molar ratio is 10 to obtain a suitable ion exchange rate, temperature and time selection, and select an appropriate amount of lithium compound to promote ion exchange. The ion exchange temperature and time are to ensure the crystal formation of the O2 phase structure, thereby obtaining a pure phase P63mc structure with a relatively perfect lattice, so that the lithium cobalt oxide positive electrode material prepared in Example 1 has excellent electrochemical properties.
[0241] Comparative Example 1 is a commonly used traditional O3 type lithium cobalt oxide on the market. Its first discharge specific capacity at 0.1C is 206.8 mAh / g, its first coulombic efficiency is 91.6%, its second week discharge specific capacity at 0.1C is 202.5 mAh / g, its 0.5C discharge specific capacity is 170.9 mAh / g, its 1.0C discharge specific capacity is 147.7 mAh / g, its discharge specific capacity after 100 cycles at 0.5C is 102.1 mAh / g, and its capacity retention rate after 100 cycles at 0.5C is only 50.3%. It can be seen that, compared with the conventional O3-type lithium cobalt oxide positive electrode material of Comparative Example 1, the lithium cobalt oxide positive electrode material of Example 1 of the present invention has an initial discharge specific capacity of 7.2 mAh / g higher at 0.1C, a discharge specific capacity of 4.2 mAh / g higher at 0.1C in the second week, a discharge specific capacity of 12.3 mAh / g higher at 0.5C, a discharge specific capacity of 24.3 mAh / g higher at 1C, a discharge specific capacity of 77.8 mAh / g higher at 0.5C after 100 cycles, and a capacity retention rate of 47.9% higher at 0.5C after 100 cycles. This shows that compared with the conventional O3-type lithium cobalt oxide positive electrode material, the lithium cobalt oxide positive electrode material with an O2 phase structure prepared by the preparation method provided by the embodiment of the present invention has excellent specific capacity, rate performance, and cycle stability under high voltage, and meets the battery's requirements for high energy density, cycle life, cycle stability, and safety performance.
[0242] The difference between Comparative Examples 2, 3 and 4 and Example 1 is that Li OH, Li2CO3 and LiNO3 are weighed according to the molar ratios m(LiOH) / n(LiOH+Li NO3)=0.1 and 0.7, and m(Li2CO3) / n(Li2CO3+Li NO3)=0.7, respectively.
[0243] The first discharge specific capacities of Comparative Examples 2-4 at 0.1C are 188.5mAh / g, 118.5mAh / g and 116.9mAh / g, the first coulombic efficiencies are 79.3%, 80.5% and 88.7%, the second week discharge specific capacities at 0.1C are 176.6mAh / g, 115.3mAh / g and 114.5mAh / g, the 0.5C discharge specific capacities are 175.9mAh / g, 104.3mAh / g and 108.5mAh / g, the 1C discharge specific capacities are 158.6mAh / g, 90.2mAh / g and 89.5mAh / g, the discharge specific capacity of Comparative Example 2 after 100 cycles at 0.5C is 105.2mAh / g, and the capacity retention rates after 100 cycles at 0.5C are 66.3%. It can be seen that, relative to the lithium cobalt oxide materials of Comparative Examples 2-4, the first discharge specific capacity of the positive electrode material of Example 1 at 0.1C is 25.5 mAh / g, 95.5 mAh / g, and 97.1 mAh / g higher, respectively, and the first coulombic efficiency is 12.9%, 11.7%, and 3.5% higher, respectively. The second week discharge specific capacity at 0.1C is 30.1 mAh / g, 91.4 mAh / g, and 92.2 mAh / g higher, respectively. The 0.5C discharge specific capacity is 7.3 mAh / g, 78.9 mAh / g, and 74.7 mAh / g higher, and the 1.0C discharge specific capacity is 13.4 mAh / g, 81.8 mAh / g, and 82.5 mAh / g higher. Relative to Comparative Example 2, the discharge specific capacity of Example 1 after 100 cycles at 0.5C is 74.7 mAh / g higher, and the capacity retention rate after 100 cycles at 0.5C is 31.9% higher. In Comparative Example 2, m(LiOH) / n(LiOH+LiNO3)=0.1, and in Comparative Example 3, m(LiOH) / n(LiOH+LiNO3)=0.7. Although these two substances have characteristic peaks of O2 phase, their peak intensity is much lower than that of I A1 / I B1 Does not meet the conditions k·(I A1 / I B1 )=2.393-(N-0.4) 2 , 0.9≤k≤1.1, 0.2≤N≤0.6, which indicates that when the N value is too high or too low, it is difficult to obtain the required specific capacity, rate performance and cycle stability under high voltage. In Comparative Example 4, m(Li2CO3) / n(Li2CO3+LiNO3)=0.7, and there is no characteristic peak of O2 phase, which indicates that the selection of lithium compounds is crucial, and the difference in low eutectic points of different lithium compounds affects the formation of lithium cobalt oxide crystal structure.
[0244] Comparative Example 5 is different from Example 1 in that the molar ratio of Li / Na is controlled to be 1 when weighing the intermediate product. The button cell assembled in Comparative Example 5 has a first discharge capacity of 150.5 mAh / g at 0.1C, a first coulomb efficiency of 78.4%, a second week discharge capacity of 148.5 mAh / g at 0.1C, a 0.5C discharge capacity of 135.9 mAh / g, and a 1C discharge capacity of 125.8 mAh / g. It can be seen that the lithium cobalt oxide positive electrode material of Example 1 of the present invention has a first discharge capacity of 63.5 mAh / g higher than that of the lithium cobalt oxide material of Comparative Example 5 at 0.1C, a first coulomb efficiency of 13.8% higher, a second week discharge capacity of 58.2 mAh / g higher at 0.1C, a 0.5C discharge capacity of 47.3 mAh / g higher, and a 1C discharge capacity of 46.2 mAh / g higher. This indicates that a lower Li / Na ratio cannot produce a pure O2 phase lithium cobalt oxide. The lithium cobalt oxide positive electrode material with a pure O2 phase structure of the present invention has excellent specific capacity, rate performance and cycle stability under high voltage.
[0245] Comparative Example 6 is different from Example 1 in that the concentration of the lithium compound aqueous solution is 1 mol / L, and its first discharge specific capacity at 0.1C is 143.7 mAh / g, the first coulomb efficiency is 79.5%, the second week discharge specific capacity at 0.1C is 142.5 mAh / g, the 0.5C discharge specific capacity is 128.5 mAh / g, and the 1C discharge specific capacity is 114.6 mAh / g. It can be seen that although the preparation process conditions of Comparative Example 6 and the lithium cobalt oxide positive electrode material of the present invention are mostly the same, only the concentration of the lithium compound aqueous solution is significantly different, but the first discharge specific capacity of the lithium cobalt oxide positive electrode material of Example 1 at 0.1C is 70.3 mAh / g higher than that of Comparative Example 6, the first coulomb efficiency is 12.7% higher, the second week discharge specific capacity at 0.1C is 64.2 mAh / g higher, the 0.5C discharge specific capacity is 54.7 mAh / g higher, and the 1C discharge specific capacity is 57.4 mAh / g higher. This indicates that when the concentration of the lithium compound aqueous solution is too low, that is, when the concentration of the lithium salt in the preparation process is too low, the electrochemical performance of the obtained lithium cobalt oxide material is poor.
[0246] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A lithium cobalt oxide positive electrode material with an O2 phase structure, characterized in that: The general chemical formula of the lithium cobalt oxide positive electrode material is: Li 1+a (Co c M d ) (1+a) / (1+a+b) O2·X b (Co c M ’ d ) b / (1+a+b) O2, wherein -1<a≤0.1, 0<b≤1, 0<c≤1, 0≤d≤0.5, -1<a+b≤1.1, X comprises one or more elements selected from Na, K, Rb, Cs or B, and M and M' are both selected from at least one element selected from Ni, Mn, Al, Mg, Co, Cu, Ca, Zn, Zr, B, Nb, Fe, Cr, Y, La, Ce, Cd or Al; The space group of the lithium cobalt oxide positive electrode material is P63mc; The lithium cobalt oxide positive electrode material is tested by X-ray using a Co-Kα target. A1 =18.3~18.9°, 2θ A2 =37.9~38.4°, 2θ A3 =46.7~47.3° and 2θ B1 = =16.0~16.5°positions have diffraction characteristic peaks at the same time; The lithium element in the lithium cobalt oxide positive electrode material comes from a lithium compound.
2. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that The lithium compound includes a first lithium compound and a second lithium compound; wherein the first lithium compound is lithium nitrate; and the second lithium compound includes one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium iodide, lithium fluoride, lithium bromide, and lithium phosphate; The molar ratio of the amount of the second lithium compound added to the total amount of the first lithium compound and the second lithium compound added is N; wherein N=m(LiY) / n(LiY+LiNO3), m represents the molar content of the second lithium compound, n represents the sum of the molar contents of the first lithium compound and the second lithium compound, LiY represents the abbreviation of the second lithium compound, and 0.2≤N≤0.6; The lithium cobalt oxide positive electrode material has a 2θ A1 The peak intensity of the characteristic diffraction peak at is I A1 , in 2θ B1 The peak intensity of the characteristic diffraction peak at is I B1 ; I A1 , said I B1 The following relationship is satisfied with N: k·(I A1 / I B1 )=2.393-(N-0.4) 2 , where k is the correction coefficient, 0.9≤k≤1.
1.
3. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that The morphology of the lithium cobalt oxide positive electrode material is a secondary single crystal particle; the secondary single crystal particle is formed by a plurality of primary flaky particles; the thickness of the primary flaky particles is between 0.7 μm and 3.7 μm.
4. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that The median particle size D50 of the secondary particles of the lithium cobalt oxide positive electrode material is 2 μm to 18 μm; The specific surface area of the lithium cobalt oxide positive electrode material is 0.5 m 2 / g~1.0m 2 / g; The true density of the lithium cobalt oxide positive electrode material is 2 g / cm 3 ~6g / cm 3 ; The residual alkali on the surface of the lithium cobalt oxide positive electrode material is 0.5% to 2.5% based on the weight of the lithium cobalt oxide positive electrode material; Based on the weight of the lithium cobalt oxide positive electrode material, the free sodium content of the lithium cobalt oxide positive electrode material is 0.5% to 2.5%.
5. A method for preparing the lithium cobalt oxide positive electrode material with O2 phase structure as claimed in any one of claims 1 to 4, characterized in that: The preparation method comprises: Step S1, uniformly mixing a cobalt source material, a sodium source material, a material containing an M element, and a material containing an M' element according to a certain proportion to obtain a mixed material; Step S2, calcining the mixture at high temperature to obtain an intermediate product; Step S3, weighing a certain amount of lithium compound and dissolving it in pure water to obtain a lithium compound aqueous solution; Step S4, weighing the intermediate product according to a certain Li / Na molar ratio, adding it to the lithium compound aqueous solution for ion exchange, and obtaining an ion exchange product; Step S5, washing and drying the ion exchange product to obtain a lithium cobalt oxide positive electrode material.
6. The preparation method according to claim 5, characterized in that: The cobalt source material comprises one or more of cobalt oxide, cobaltous oxide, cobalt trioxide, cobalt chloride, cobalt sulfate, cobalt hydroxide, cobalt oxalate, cobalt carbonate, and organic acid cobalt; the median particle size D50 of the cobalt source material is 1 μm to 20 μm, and the specific surface area is 2.5 m 2 / g~5.5m 2 / g, tap density is 2.0g / cm 3 ~3.2g / cm 3 ; The sodium source material includes: one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium nitrate, sodium oxide, sodium peroxide, sodium sulfate, and sodium chloride; The molar number j of Co in the cobalt source material and the molar number l of Na in the sodium source material satisfy: 0.5≤l / j≤1.0, preferably 0.6≤l / j≤0.9; The M and the M' are both selected from at least one of Ni, Mn, Al, Mg, Co, Cu, Ca, Zn, Zr, B, Nb, Fe, Cr, Y, La, Ce, Cd or Al, and the M and the M' are the same metal element or different metal elements; The molar number of M is p, the molar number of M' is q, and p, q and j satisfy: (p+q) / j=0.003-0.
03.
7. The preparation method according to claim 5, characterized in that: The high temperature calcination temperature is 700°C to 1000°C, and the sintering time is 6 hours to 15 hours; The high-temperature calcination is carried out in an oxygen atmosphere, wherein the oxygen concentration is ≥ 90%.
8. The preparation method according to claim 5, characterized in that: The molar concentration of the lithium compound in the lithium compound aqueous solution is greater than or equal to 2 mol / L; the lithium compound includes a first lithium compound and a second lithium compound; wherein the first lithium compound is lithium nitrate; and the second lithium compound includes one or more of lithium hydroxide, lithium carbonate, lithium chloride, lithium iodide, lithium fluoride, lithium bromide, and lithium phosphate; The molar ratio of the added amount of the second lithium compound to the total added amount of the first lithium compound and the second lithium compound is N; wherein N=m(LiY) / n(LiY+LiNO3), m represents the molar content of the second lithium compound, n represents the sum of the molar contents of the first lithium compound and the second lithium compound, LiY represents the abbreviation of the second lithium compound, and 0.2≤N≤0.
6.
9. The preparation method according to claim 5, characterized in that: The molar ratio of Li / Na is greater than or equal to 5; the temperature of the ion exchange is greater than or equal to 80° C., and the time of the ion exchange is greater than or equal to 8 hours.
10. An energy storage device, characterized in that: The energy storage device contains the lithium cobalt oxide positive electrode material described in any one of claims 1 to 4 or the lithium cobalt oxide positive electrode material obtained by the preparation method of any one of claims 5 to 9; the energy storage device is a lithium battery or a battery cell composed of lithium batteries.
Citation Information
Patent Citations
Lithium composite metal oxides and nonaqueous-electrolyte secondary cell
CN101541684A
Positive electrode material, electrochemical device, and electronic apparatus
CN113597693A
Lithium-rich positive electrode material, preparation method thereof and lithium ion battery
CN115881943A
Lithium cobalt oxide positive electrode material, preparation method thereof and secondary battery
CN118538910A
Cobalt oxide for lithium secondary battery, preparing method thereof, lithium cobalt oxide formed therefrom, and lithium secondary battery including positive electrode comprising the lithium cobalt oxide
KR1020180029910A
Cited By
Cobaltosic oxide for O2-phase lithium cobalt oxide as well as preparation method and application of cobaltosic oxide
CN120681793A
Positive electrode material, electrochemical device, and electronic device
WO2026207672A1
